2015
DOI: 10.1111/jsr.12291
|View full text |Cite
|
Sign up to set email alerts
|

Sleep inertia, sleep homeostatic and circadian influences on higher‐order cognitive functions

Abstract: Summary Sleep inertia, sleep homeostatic, and circadian processes modulate cognition, including reaction time, memory, mood, and alertness. How these processes influence higher-order cognitive functions is not well known. Six participants completed a 73-daylong study that included two 14-daylong 28h forced desynchrony protocols, to examine separate and interacting influences of sleep inertia, sleep homeostasis, and circadian phase on higher-order cognitive functions of inhibitory control and selective visual a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
124
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(136 citation statements)
references
References 34 publications
11
124
1
Order By: Relevance
“…This finding is in accordance with the results obtained in a similar forced desynchrony protocol (26) and in a quantitative analysis of the effects of 36 h of wakefulness across nearly 1.5 circadian cycles (51). In accordance with previous observations (27)(28)(29), both the linear and nonlinear analyses demonstrated that the effects of time awake and circadian phase interacted: The deterioration with time awake is most pronounced in the early morning; in other words, the effect of circadian phase on performance very much depends on time awake.…”
Section: Circadian and Time Awake-dependent Regulation Of Waking Funcsupporting
confidence: 83%
See 2 more Smart Citations
“…This finding is in accordance with the results obtained in a similar forced desynchrony protocol (26) and in a quantitative analysis of the effects of 36 h of wakefulness across nearly 1.5 circadian cycles (51). In accordance with previous observations (27)(28)(29), both the linear and nonlinear analyses demonstrated that the effects of time awake and circadian phase interacted: The deterioration with time awake is most pronounced in the early morning; in other words, the effect of circadian phase on performance very much depends on time awake.…”
Section: Circadian and Time Awake-dependent Regulation Of Waking Funcsupporting
confidence: 83%
“…In the present study, the deterioration of brain function was observed even though time awake varied only between 0 and ∼19 h. This deterioration was modulated by circadian phase so that it was more pronounced when wakefulness coincided with the phase of melatonin secretion, i.e., the biological night. In one previous study with a number of tasks similar to that in our study, circadian effect sizes for sleepiness and attention were relatively pronounced, in accordance with the current study (26). However, inhibition was more affected by circadian phase in that study than in our study, where aspects of inhibition assessed in SART did not show comparably large circadian effects.…”
Section: Circadian and Time Awake-dependent Regulation Of Waking Funccontrasting
confidence: 37%
See 1 more Smart Citation
“…Controlling for both circadian phase and homeostatic sleep pressure using a forced desynchrony protocol, Scheer et al (34) demonstrated that the effect of sleep inertia on performance was gone within 20 min across all circadian phases. Conversely, others, albeit using protocols that did not assess throughout all circadian phases (35) or with infrequent assessments postawakening (36), have reported that sleep inertia can take longer periods to dissipate (between 2 and 4 h). We also did not include an objective measure of performance, although our results are consistent with those of others who did (25).…”
Section: Discussionmentioning
confidence: 99%
“…In a forced desynchrony protocol designed to tease apart these factors, Burke et al demonstrated that the largest effect sizes from sleep inertia were on selective visual attention (on a spatial search task) and subjective sleepiness [40]. Forced desynchrony studies have confirmed that impaired performance on awakening is most prominent during the biological night, when awakening at or within 120° before the core body temperature minimum [41, 42].…”
Section: Experimental Manipulation: Factors That Increase Sleep Inertiamentioning
confidence: 99%